RANCANGAN ANNOUNCEMENT TARUNA MELALUI APLIKASI PUBLIC ADDRESS SYSTEM TEXT TO SPEECH DI KANTOR TARUNA JAGA STPI - Ariyanto Subekti; Zulina Kurniawati; Parjan (Politeknik Penerbangan Indonesia Curug, 2019)
Announcement is a statement in oral or written form that contains information for many to know. In giving announcements of cadets in charge there are still many mistakes, therefore an application program that can make it easier for cadets in charge to provide daily service provision information at the STPI is needed. The design of this application program aims to provide suggestions in the form of announcement for cadets through the text to speech public address system application by using the Sublime Text 3 and the Hypertext Preprocessor (PHP) programming language which are expected to help cadets in charge and can reduce errors that often occur.This application program can be implemented at the cadets office to improve the service of providing information on retention without reducing the learning available for cadets of the STPI Curug